School exclusion disparities in the UK: a view from Northern Ireland. Issue 1 (2nd January 2021) - Duffy, Gavin; Robinson, Gareth; Gallagher, Tony; Templeton, Michelle
ABSTRACT: Across the four UK jurisdictions, there are distinct disparities in exclusion rates of school students. Northern Ireland, alongside Scotland and Wales, has demonstrated over time, lower rates of permanent exclusions and temporary exclusions compared with England. This paper examines these disparities from the perspectives of representatives from various system-level educational bodies and third sector organisations representing children and families who experienced the exclusion process. The paper will also present policy and legal frameworks associated with exclusion in Northern Ireland. We interviewed 9 stakeholders, associated with practices of school exclusion in Northern Ireland, from a range of system-level education bodies and advocacy groups. Findings include positive strategies perceived to keep exclusion levels low, types of obstacles or resistance to anti-exclusion policy, participants' perspectives on unofficial exclusion practice, and perspectives on official exclusion data. What emerges from interviews is a series of tensions between implementing a child-centred approach and diminishing support services and resources. We conclude that those working within the Northern Ireland education system, are committed to an inclusive approach. However, the development and implementation of effective supporting frameworks take time and consultation, and there is evidence of tension between the perceptions of those working at a system-level and those working in schools.